2018
DOI: 10.1097/pec.0000000000001483
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship Between Clinical and Laboratory Characteristics in Children With Severe Scorpion Envenomation in Çukurova, Turkey

Abstract: Objective Scorpion stings are an important health problem in many parts of the world. The aim of this study was to retrospectively examine cases of scorpion stings to evaluate their epidemiological, clinical, and laboratory features and to determine strategies that can reduce morbidity and mortality in these cases. Methods Scorpion stings experienced by children between 2007 and 2013 were retrospectively reviewed. The patients were categorized into grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Most cases of severe envenomation occur in children and are associated with morbidity and mortality. 9 Although there is no accurate data worldwide, a 20% mortality rate is reported in untreated infants and 10% in untreated school-aged children. 10 Many studies have been conducted recently with the help of hematological parameters, especially, the ratio between the absolute number of neutrophils and the number of lymphocytes has been considered as a potential new biomarker predicting the worse clinical course of cancer, infectious diseases, cardiovascular diseases, end-stage renal disease, immunologic diseases, and schizophrenia.…”
mentioning
confidence: 99%
“…Most cases of severe envenomation occur in children and are associated with morbidity and mortality. 9 Although there is no accurate data worldwide, a 20% mortality rate is reported in untreated infants and 10% in untreated school-aged children. 10 Many studies have been conducted recently with the help of hematological parameters, especially, the ratio between the absolute number of neutrophils and the number of lymphocytes has been considered as a potential new biomarker predicting the worse clinical course of cancer, infectious diseases, cardiovascular diseases, end-stage renal disease, immunologic diseases, and schizophrenia.…”
mentioning
confidence: 99%
“…3 In a study with 64 patients in Turkey, the death rate was 12%; the death rate in another study was reported as 0%. 8,9 Similarly, none of the patients in our research died (0%). So far, 13 species from 8 families have been identified, including Buthidae, Chacthida, Iurida, and Scorpionidae families in Turkey.…”
Section: Discussionmentioning
confidence: 53%
“…The most common symptom after a scorpion sting is pain at the site of the sting. 6,7,12,17,18 In cases of scorpion stings without systemic findings, providing analgesia is one of the most important steps of emergency intervention. However, as stated in a meta-analysis, there are insufficient studies that determine the analgesic(s) that are most effective for scorpion stings.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 The type, age, and size of the scorpion, nutritional status, number of stings, venom injection depth, the sting being located closer to the head and neck, and age and health status of the patient may affect the clinical course. 6 Scorpion venoms are mixtures of many biologically active components, some of which are hemolysins and neurotoxins; the latter often act on ion channels. 7 When bound to these channels, inactivation is inhibited, leading to neuroexcitation and thus prolonged depolarization.…”
Section: Introductionmentioning
confidence: 99%